The Role of DPP4 Activity in Cardiovascular Districts: In Vivo and In Vitro Evidence. (18th June 2013) - Pala, L.; Rotella, C. M.
Abstract : The introduction of incretin hormone-based therapies represents a novel therapeutic strategy, since these drugs not only improve glycemia with minimal risk of hypoglycemia, but also have other extraglycemic beneficial effects. These agents, which are effective in improving glucose control, could also have positive effects on the incidence of cardiovascular events. The aim of this review is to summarize the present literature about the role of dipeptidyl peptidase 4 (DPP4) in cardiovascular districts, not only strictly correlated to its effect on glucagon-like peptide-1 (GLP-1) circulating levels, but also to what is known about possible cardiovascular actions. Actually, DPP4 is known to be present in many cells and tissues and its effects go beyond purely metabolic aspects. Almost always the inhibition of DPP4 activity is associated with improved cardiovascular profile, but it has shown to possess antithrombotic properties and these different effects could be connected with a site and/or species specificity of DPP4. Certainly, DPP4 seems to exert many functions, both directly and indirectly, on cardiovascular districts, opening new possibilities of prevention and treatment of complications at this level, not only in patients affected by diabetes mellitus.